Entrepreneur-investor information design - Oleg Muratov (University of Bern, Department of Economics, 2020)
I consider an environment in which the entrepreneur generates information about the quality of the projects prior to contracting with the investor. The investor faces a moral hazard problem, since the entrepreneur may divert the funding for private consumption. When the investor bargains with the entrepreneur, I find that the efficient amount of information is generated if and only if the bargaining power of the entrepreneur is high enough. I interpret this result in terms of investors' concentration, competitiveness, and generosity measures. I show that the investor prefers a non-absolute bargaining power when the project costs are high enough.
Keywords: 330; Unternehmer; Investor Relations; Verhandlungsmacht; Investitionsentscheidung; Informationsökonomik; Moral Hazard; Theorie